1993
DOI: 10.1115/1.2921667
|View full text |Cite
|
Sign up to set email alerts
|

Observations of Shear Localization in Liquid Lubricants Under Pressure

Abstract: A High Pressure Flow Visualization Cell has been designed and constructed to perform a fundamental investigation of the deformation behavior of liquid lubricants under lubricated concentrated contact conditions. A pressure of 0.3 GPa and a shear stress between parallel plates of about 25 MPa has been demonstrated. Time averaged velocity profiles show no continuous slip either in the bulk or at walls. Localized slip at shear bands inclined to the walls was demonstrated to occur during nonlinear shear response. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(34 citation statements)
references
References 0 publications
3
31
0
Order By: Relevance
“…In the field of tribology, shear localisation has only been directly observed experimentally in viscous model lubricants, such as polybutadiene and polyphenyl ethers (e.g., 5P4E) [196][197][198][199][200][201]. However, it has also been inferred from film thickness measurements in realistic mineral oils [202,203] and there is currently a growing consensus that this phenomenon may also be important for more realistic lubricants under extreme EHL conditions [185].…”
Section: Shear Localisationmentioning
confidence: 96%
“…In the field of tribology, shear localisation has only been directly observed experimentally in viscous model lubricants, such as polybutadiene and polyphenyl ethers (e.g., 5P4E) [196][197][198][199][200][201]. However, it has also been inferred from film thickness measurements in realistic mineral oils [202,203] and there is currently a growing consensus that this phenomenon may also be important for more realistic lubricants under extreme EHL conditions [185].…”
Section: Shear Localisationmentioning
confidence: 96%
“…It is conceivable that when the applied shear stress exceeds this value, slip may occur within the lubricant film. Some evidence to support was provided by Bair et al [23], albeit for considerably thickener films, which showed oil samples within a high pressure rheometer that fractured under high pressure forming slip bands [23]. Recently, important work by Ponjavic et al [24], using fluorescence microscopy to obtain through-thickness velocity profiles, has shown that oligomer polybutene exhibits wall-slip under EHL conditions [24].…”
Section: Introductionmentioning
confidence: 92%
“…This assumption requires verification as there is a possibility that slip occurs at a point midway through the thickness of the film, as for instance observed by Bair [23] using a high pressure rheometer.…”
Section: Location Of Slip and Validation Of Assumptionmentioning
confidence: 99%
“…In 1993 Bair and Winer studied velocity profiles by tracking micro-sized dispersed particles in three lubricants sheared between two flat surfaces at high shear stress [106]. The lubricant films were observed from the side, which meant that their thickness, of 150 m, was much greater than a normal EHD film.…”
Section: Probing the Velocity Profile In Ehd Contactmentioning
confidence: 99%